KEGIATAN STORYTELLING DALAM PENINGKATKAN KETERAMPILAN BERBAHASA ANAK DI PERPUSTAKAAN KOBER AL-QOLAM - Iqbal Kesuma; Rifqi Zaeni Achmad Syam; Oom Nurrohmah (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2022)
This study aims to determine the application of storytelling activities in improving the language skills of children aged 5 to 6 years at the Kober Al-Qolam Library Bandung which is seen from the listening aspect, speaking aspect, writing aspect and reading aspect. This research is a qualitative descriptive study involving teachers and principals. Data were collected through interviews, observation and document analysis. Data analysis through data collection, data reduction, data presentation and drawing conclusions. The results showed that the application of storytelling activities was able to improve language skills in Kober Al-Qolam. This can be seen in several aspects, namely in the listening aspect, which occurs when the teacher is able to attract children's attention when telling stories. In the speaking aspect, it occurs when the teacher provides a stimulus in the form of questions to the child and the child can answer the teacher's question. As for the writing aspect and the reading aspect, it occurs when the teacher gives orders to the child to write the character in the story, for example when asked to write the name of the character